Tropospheric moisture and its relation with rainfall due to nor’westers in Bangladesh (MAUSAM, 2007)
Attempts have been made to compute the precipitable water content of the troposphere, weighted average water vapour and to correlate these parameters with different instability indices and also with the next 24-hr rainfall, next 24-hr maximum rainfall and next 24-hr country averaged rainfall in order to predicting rainfall due to nor’westers in Bangladesh. It has been found that the maximum number of nor’westers occur when the precipitable water is 25-45 mm hr-1 between 1000 and 500 hPa, the maximum frequency being 48 in the range of 35-45 mm hr-1. The spatial distribution of precipitable water indicates that the maximum precipitable water is concentrated over the area near the places of nor’westers. The specific humidity has been found to increase on the dates of occurrence of nor’westers in Bangladesh on most occasions. Maximum number of nor’westers occurs when the weighted average specific humidity between the surface (1000 hPa) and 500 hPa is 8-12 g kg-1, the maximum frequency being 43 in the range of 8-10 g kg-1. The study reveals that nor’westers have been found to occur near or at the eastern end of maximum weighted average specific humidity. It has also been found that nor’westers occur near the point of inter-section of the axes of moist and dry zones. A number of parameters of the troposphere over Dhaka at 0000 UTC on the dates of occurrence of nor’westers such as precipitable water (mm/hr), MSWI, SWI, SWI/TT, (q1000 – q850) weighted averaged specific humidity have statistically significant correlations with next 24-hour rainfall at Dhaka, next 24-hour maximum rainfall in Bangladesh and country averaged rainfall. The correlation co-efficients are relatively small and the standard errors of estimates are higher. The small correlation co-efficients are significant because of the large number of data.